Reason and revelation before historicism : Strauss and Fackenheim - Portnoff, Sharon (University of Toronto Press, 2011)
"Can contemporary religion, and particularly Judaism, exist without being informed by history? This question was debated in 1940s New York by two German refugees who later rose to prominence -- Leo Strauss, one of the twentieth century's most significant political philosophers, and Emil L. Fackenheim, an important post-Holocaust Jewish theologian. There has been little consensus, however, on the definitive meaning of their work. Reason and Revelation before Historicism, the first full-length comparison of Strauss and Fackenheim, places the informal teacher and student in conversation alongside sections of their analyses of notable thinkers. Sharon Portnoff suggests that both saw historicism as the nexus of the intersection and tension between philosophy and religion and raised the possibility of the persistence of the permanent in the modern world. Portnoff illuminates our understanding of Strauss's relationship with Judaism, Fackenheim's oft-overshadowed great philosophical depth, and the function and character of Jewish thought in a secular, post-Holocaust world."--Publisher's website.